Drought and consumption impacts of climate-smart-agricultural practices adoption in drought prone area of Eastern Hararghe, Ethiopia - Jafer Mume Ahmed; Jema Haji; Moti Jaleta; Kedir Jemal (Agricultural Water Management, 2025)
Annual consumption expenditure of the households is seriously affected by climate shocks in the country where the major livelihood of the community depends on rain-based agriculture. Multinomial endogenous switching regression (MESR) model was applied to analyze factors affecting adoption of climate smart agricultural practices and impact of adoption on consumption expenditure in Eastern Hararghe, Ethiopia. Irrigation, crop diversification and integrated soil fertility management were widely practiced in the study area. From East Hararghe zone four districts were randomly selected. The primary data was collected from 430 sample respondents during 2023 year. Using the rainfall data of 33 years, drought was analyzed by using standard precipitation index (SPI). The model result revealed that education of the family head, family size, livestock, market information, drought experience, climate information and drought significantly influenced the adoption of climate smart agricultural practice (CSAPr). The result showed that, the highest consumption expenditure was obtained when farmers adopted combination of crop diversification and irrigation practices (F0D1I1) which is 12610.9ETB. The adopters also obtained 11274ETB when they adopted integrated soil fertility and crop diversification (F1D1I0). All adopters obtained higher consumption expenditure per adult as compared to the non-adopters (F0D0I0) which is 9434.5ETB. It also showed that, out of total consumption increased by adoption of CSAPr, 72.4 percent of incensement was obtained by adopting practices combination whereas 27.6 percent was by single practices. So, it is very important to advance farmers’ information on drought and adoption strategy. The policymakers ought to develop and encourage farmers’ asset building plan, adult education, market linkage facilities and extension service and weather information delivery system to enhance adoption of CSAPr practices to combat the current and future drought. Therefore, the study recommends that policies should promote joint adoption of climate smart practices in drought prone area to increase climate change mitigation and consumption expenditure.